Análisis por Elementos Finitos del Coeficiente de Fricción en un Modelo Poro-Elastohidrodinámico de Junta Sinovial - Di Paolo, J.; Corvalán, C. V.; Saita, F. A. (Revista Mexicana de Ingenieria Biomedica, 1999)
Computational results of a simple mechanical model having common characteristics with synovial joints are presented. The model describes the lubrication phenomenon taking place between two cylindrical surfaces covered by elasto-porous materials. Deformations, pressures and exudations on the lubricated surfaces are locally calculated as well as the amount of lubricating liquid flowing between them. For that purpose, the employed F.E.M is coupled with suitable techniques to parameterize the unknown location of the outflow boundary with zero pressure gradient. Several conclusions are presented regarding the self-lubricating and low friction characteristics of synovial joints and their connections with the liquid exuded by the porous surfaces.